Assessment of nutritional status with its associated factors in pregnant women attending antenatal care at Ambo Health Centers, Oromia Region, Ethiopia - Fekadu, Tsige; Gashaw, Fikru; Bekele, Damtew (Journal of Medicine and Health Sciences Research, 2024)
Nutritional status during pregnancy, maternal nutrition requires considerable attention; however, pregnant women’s nutritional knowledge and practices are less understood. The objective of this study was to assess nutritional knowledge and practices among pregnant women who attend antenatal care at Ambo and Awaro Health Center of Ambo Town, Oromia Region, Ethiopia. The study was conducted from January to May of the year 2022, using a cross-sectional descriptive study on a sample of 284 pregnant women who attended antenatal care services in Awaro and Ambo health centers. Systematic sampling techniques were used to select pregnant mothers by using Health center registration lists. Socio-demographic and socio-economic data were collected using a structured interviewer-administered questionnaire. Mid-Upper Arm Circumference (MUAC) was measured by standard nonstretchable MUAC tape. Binary and multiple logistic regression analysis was conducted using the Statistical Package for Social Sciences (SPSS) program version 20 for further analysis. The finding of associated factors that affect the nutritional status of mothers was the income level of the family has a strong statistical association with the nutritional status of mothers (p<0.001), occupational status of the respondent has a significant association with nutritional status (p<0.05) and also knowledge about the importance of food for growth and development of fetus of mother have significant association (p<0.05). Hence, the government in collaboration with concerned bodies should focus on nutritional education and information of pregnant mothers on maternal nutrition during pregnancy in the study area.